PDBe: improved accessibility of macromolecular structure data from PDB and EMDB. Issue Volume 44:Issue D1(2016) (17th October 2015) - Velankar, Sameer; van Ginkel, Glen; Alhroub, Younes; Battle, Gary M.; Berrisford, John M.; Conroy, Matthew J.; Dana, Jose M.; Gore, Swanand P.; Gutmanas, Aleksandras; Haslam, Pauline; Hendrickx, Pieter M. S.; Lagerstedt, Ingvar; et al.
Abstract: The Protein Data Bank in Europe (http://pdbe.org ) accepts and annotates depositions of macromolecular structure data in the PDB and EMDB archives and enriches, integrates and disseminates structural information in a variety of ways. The PDBe website has been redesigned based on an analysis of user requirements, and now offers intuitive access to improved and value-added macromolecular structure information. Unique value-added information includes lists of reviews and research articles that cite or mention PDB entries as well as access to figures and legends from full-text open-access publications that describe PDB entries. A powerful new query system not only shows all the PDB entries that match a given query, but also shows the 'best structures' for a given macromolecule, ligand complex or sequence family using data-quality information from the wwPDB validation reports. A PDBe RESTful API has been developed to provide unified access to macromolecular structure data available in the PDB and EMDB archives as well as value-added annotations, e.g. regarding structure quality and up-to-date cross-reference information from the SIFTS resource. Taken together, these new developments facilitate unified access to macromolecular structure data in an intuitive way for non-expert users and support expert users in analysing macromolecular structure data.